1987
DOI: 10.1177/0734242x8700500134
|View full text |Cite
|
Sign up to set email alerts
|

Impact On Health of Chlorinated Dioxins and Other Trace Organic Emissions

Abstract: The potential health effects of incineration of municipal solid waste (MSW) have been studied by the Swedish National Institute of Environmental Medicine. The greatest concern for health effects relates to the emission of PCDDs and PCDFs ("dioxins"). MSW incineration is presently estimated to be a large source for the emission of these compounds into ambient air. Based upon animal experiments, and by applying safety factors in the range 200-1000, a highest tolerable daily intake (TDI) has been estimated to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The dominating source is the food. 3 CONCLUSION Based on the case study, exposure calculations, scrutiny of registers and study of the literature, we conclude that discharge of dioxin cannot explain the observed clusters of cleft lip and palate. The groups studied are small and small numbers are unstable from a statistical point of view.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The dominating source is the food. 3 CONCLUSION Based on the case study, exposure calculations, scrutiny of registers and study of the literature, we conclude that discharge of dioxin cannot explain the observed clusters of cleft lip and palate. The groups studied are small and small numbers are unstable from a statistical point of view.…”
Section: Discussionmentioning
confidence: 94%
“…The concentrations of dioxin caused by discharge from incinerators were judged to be below those that are harmful to man by inhalation. 3 In some cases, however, a local accumulation of cleft lip and palate has been related to refuse incineration. 4 An analysis of the incidence of the relevant type of malformation in all boroughs with incinerators was therefore considered warranted.…”
Section: Introductionmentioning
confidence: 99%
“…That energy recovery by heat and electricity production from waste incineration and wastewater treatment as accounted for in Table 2 are associated with significant improvements in environmental protection due to technology advances over the past two to three decades. For example, Ahlborg and Victorin (1987) shows that dioxin emissions in Sweden amounted to 64 mg tonne À1 in 1985; but during the period 2007-2010 the stack emission from the waste incinerator in Malmo¨amounted to 64 ng tonne À1 waste incinerated according to Avfallsverige (2011); namely a factor 1000 reduction. For the Aalborg incinerator the range of variation in 1) but also recovery of glass, metals, paper and cardboard, and use of saved wood (saved due to recycling of paper and cardboard) as a bio-fuel that substitutes for use of fossil fuel (coal).…”
Section: Waste Prevention and Waste Management As Aspects Of Sustainable Developmentmentioning
confidence: 99%